KGB : State Within a State : The Secret Police and Its Hold on Russia's Past, Present, and Future - Albats, Yevgenia (London I.B. Tauris, 1995)
Explodes the myth that the KGB died - or even faded away - upon the collapse of the Soviet empire. Albats claims that the KGB actually engineered the policy of perestroika, subtly controlling the overhaul of Soviet society in order to reposition itself at the top.
Include Notes and Index
Keywords: Soviet Union -- Attempted coup (Soviet Union : 1991) -- Politics and government